PEMBINAAN PEMBELAJARAN BACA TULIS AL QUR’AN (BTQ) MELALUI METODE QIRO’ATI DI KELURAHAN SUMBER WETAN KOTA PROBOLINGGO - Tiyas, Mutiah Cahyaning; Chomaidah, Siti; Sa’diyah, Nur Halimatus; Aimmah, Agus Nashihul; Prasetiya, Benny (DEVELOPMENT: Journal of Community Engagement, 2024)
The development of learning to read and write the Qur'an (BTQ) using the Qiro'ati method in Sumber Wetan Village, Probolinggo City was carried out with research aimed at improving understanding and mastery of reading the Qur'an in elementary school-age children up to teenagers. Data collection methods involve coaching activities, observation, interviews, and documentation. This research uses the Qiro'ati method as a learning approach, with stages of preparation, implementation, and evaluation. This research was carried out through the community service method with a qualitative descriptive approach. The research results show that the Qiro'ati method can help children understand Al-Qur'an reading, master the science of tajwid, and read ghorib readings well. It is hoped that fostering BTQ learning through the Qiro'ati method can provide significant benefits for children in Sumber Wetan Village, Probolinggo City in understanding and applying the teachings of the Koran in everyday life.